A apropriação da escrita por alunos da 3ª fase do I ciclo : um estudo com sequências didáticas - Silva, Joselita Maria Silva e (2014)
This research was developed in the graduate program in education at the Universidade Federal de Mato Grosso, Rondonópolis campus and inside the ALFALE research group. Presents an approach in the teaching of textual genre fable through didactic sequences. Come across children with problems of textual production, during the teaching, motivated the investigation of the phenomenon. Similarly, issues like a low performance in writing and the grounds of the school doesn't always handle produce competent writers, future citizens aware and critics inserted in society. The doubt that if to intensify work with textual production would result in a better learning emerged, as well as which procedure permanent this appropriation. The overall objective of the study is to assess the contribution of the didactic sequences for learning of textual genres for students of the early years of elementary school and the specifics are to understand how the didactic sequences, while pedagogical instrument, interfere in the appropriation of the text genres by students; investigate the relationships between the didactic strategies by means of didactic sequences and results about the textual production capacities of students; evaluate the progress achieved during the teaching process by means of didactic sequences in the productions of textual students. Bakhtin and other textual genres which address theoretical underlying the study. The didactic sequences, in perspectives of Dolz, Noverraz and Schneuwly, contributed to the writing of texts ownership of students. The research methodology had intervention slant, using interviews with teachers, classroom observation and planning set of didactic sequences, focusing on two classes of phase 3 of the first cycle of a total of 47 public school students. Of these, 12 were selected as evaluation criterion of Municipal Education Assessment System (LEAVE), of which the texts were analyzed. Data analysis was performed taking into account the General category "Fitness to the genre", as a means of checking whether the texts if not appropriate, organised partly or completely suited to the written proposal. Secondarily, were established subcategories: the Intertextuality in writing); b) ownership/consolidation of writing; c) punctuation marks and d) brands of orality in written. The results showed that the initial productions, 2 students have addressed his writings to the genre of partial form, 7 non-suited and 3 completely. Were worked in didactic sequences activities, which helped students better understand the genres covered and thus the final productions, 2 students have adapted their texts partially, 4 non-suitable and 6 completely to the fable genre. These results allow to conclude that if that teaching is taught through didactic sequences, the possibilities of success in the appropriation of writing by students will be bigger.